The Halotolerant Rhizobacterium—Pseudomonas koreensis MU2 Enhances Inorganic Silicon and Phosphorus Use Efficiency and Augments Salt Stress Tolerance in Soybean (Glycine max L.) - Arjun Adhikari; Muhammad Aaqil Khan; Ko-Eun Lee; Sang-Mo Kang; Sanjeev Kumar Dhungana; Narayan Bhusal; In-Jung Lee (Microorganisms, 2020)
Optimizing nutrient usage in plants is vital for a sustainable yield under biotic and abiotic stresses. Since silicon and phosphorus are considered key elements for plant growth, this study assessed the efficient supplementation strategy of silicon and phosphorus in soybean plants under salt stress through inoculation using the rhizospheric strain—Pseudomonas koreensis MU2. The screening analysis of MU2 showed its high salt-tolerant potential, which solubilizes both silicate and phosphate. The isolate, MU2 produced gibberellic acid (GA1, GA3) and organic acids (malic acid, citric acid, acetic acid, and tartaric acid) in pure culture under both normal and salt-stressed conditions. The combined application of MU2, silicon, and phosphorus significantly improved silicon and phosphorus uptake, reduced Na+ ion influx by 70%, and enhanced K+ uptake by 46% in the shoots of soybean plants grown under salt-stress conditions. MU2 inoculation upregulated the salt-resistant genes GmST1, GmSALT3, and GmAKT2, which significantly reduced the endogenous hormones abscisic acid and jasmonic acid while, it enhanced the salicylic acid content of soybean. In addition, MU2 inoculation strengthened the host’s antioxidant system through the reduction of lipid peroxidation and proline while, it enhanced the reduced glutathione content. Moreover, MU2 inoculation promoted root and shoot length, plant biomass, and the chlorophyll content of soybean plants. These findings suggest that MU2 could be a potential biofertilizer catalyst for the amplification of the use efficiency of silicon and phosphorus fertilizers to mitigate salt stress.